The impact of work on the health of nursing professionals - Pimenta, Cláudia Jeane Lopes; Silva, Cleane Rosa Ribeiro da; Bezerra, Thaíse Alves; Costa, Tatiana Ferreira da; Oliveira, Jacira dos Santos; Costa, Kátia Neyla de Freitas Macedo (Revista da Escola de Enfermagem da USP, 2020)
Objective: To evaluate the impact of work on nursing professionals’ health. Method: This is a cross-sectional and quantitative study conducted with nurses from a university hospital in João Pessoa, Paraíba, Brazil. Data were collected through interviews using an instrument to obtain sociodemographic data and health conditions and the Pleasure and Suffering Indicators at Work Scale (PSIWS). Results: There were 152 nurses who participated. The Experience of Pleasure and its domains were rated as satisfactory, while Suffering Factors and their domains were critically evaluated. Statistically significant associations were observed (p≤0.05) between the indicators of pleasure and suffering and some health conditions, health problems and medication use. Conclusion: Satisfactory levels of pleasure were associated with better health conditions and critical levels of suffering were associated with worse health conditions.